Comparison of Eight Month Coastal Polluted Porcelain and Epoxy Resin Outdoor Insulators - Waluyo Waluyo; Ngapuli I. Sinisuka; Parouli M. Pakpahan; Suwarno Suwarno; Maman A. Djauhari (Journal of Engineering and Technological Sciences, 2008)
This study  presents the experimental results of eight months naturally coastal polluted outdoor porcelain  and  epoxy resin  insulators. The experiments were leakage current and applied high voltage measurements used a two-channel storage  digital  oscilloscope,  in  the  hermetically  sealed  chamber,  where temperature,  humidity ,  pressure  and  applied  voltage  could  be  adjusted  and measured simultaneously. The leakage current waveforms were analyzed using FFT  and  the  relation  to  environmental  parameters  were  analyzed  using correlation  matrix  of  multivariate  statistical  tools.  It  was  also  conducted  SEM and EDAX tests. Base  on  the  correlation  coefficient  matrix, the humidity  contributed  to  leakage current  amplitude  and  phase  angle  on  the  porcelain  insulator   were  very significant,  with  the  correlation  coefficient  were  0.60  and  -0.68  respectively. Whereas,  on  polluted  epoxy  resin  insulator,  the  humidity  did  not  influence  to leakage  current  and  phase  angle  considerably.  Generally,  the  surface  became rougher than  the new one. The most three  chemical elements in pollutants  were chlorine, silicon and ferrum.